Prenha e ferida: exegese de êxodo 21,22-25 em diálogo com a atualidade - Sousa, Maria Gisele Canário de (2017)
Law in the Hebrew Bible undergoes a paradigm shift: Laws that are restricted to civil society are now regulated by officially religious Laws. This analysis seeks to understand a casuistic Law that addresses the situation of a pregnant woman, because there is the risk of miscarriage if he would hit her by during the fight, as penalty will be imposed the Law of Talion. Through exegetical, historical, theological and social analysis; Beginning with the translation of the Hebrew text, a legal understanding of Exodus 21: 22-25 will be sought from the perspective of the pregnant woman. From the analysis comes a brief understanding of the civil and religious law in today's society of Brazil and the Magisterium of the Catholic Church. In despite of the laws seek to protect the pregnant woman, it is not full protection yet